PELATIHAN DAN PENDAMPINGAN KEMAMPUAN LITERASI MEMBACA MELALUI PROGRAM KAMPUS MENGAJAR ANGKATAN 5 PADA SISWA KELAS 5 SD NEGERI 1 KRIKILAN SRAGEN - Putri, Mufida Awalia (STAI Ma'had Aly Al-Hikam Malang, 2023)
Abstract Reading Literacy skills in the Industry 4.0 era are very important to develop because in this era everything uses the internet. The main capital in utilizing the internet is reading literacy which is then developed into digital literacy. The government is currently implementing a program to increase reading literacy skills. Reading literacy skills at SDN Krikilan 1 Masaran are not yet optimal. This is known from the Reading Literacy pre-test scores of grade 5 students which are still below 50, an average of 44.4. Community Service Activities from the Campus Teaching 5 (KM 5) program aim to improve the reading literacy skills of grade 5 students while increasing AKM scores. This training and mentoring activity is carried out by means of lectures, demonstrations, games and discussions with the help of various types of learning support media such as games, scrapbooks and story books. Next, get into the habit of reading storybooks, scrapbooks, and answering the questions in them and making summaries. The post-test results showed an average increase of 86.17, this shows an increase in the reading literacy of grade 5 students. Keywords: Reading Literacy, games media, scrapbook media Abstrak Keterampilan Literasi Membaca di era Industri 4.0 sangat penting untuk dikembangkan karena di era ini segala sesuatunya menggunakan internet. Modal utama dalam memanfaatkan internet adalah literasi membaca yang kemudian dikembangkan menjadi literasi digital. Pemerintah saat ini sedang melaksanakan program peningkatan kemampuan literasi membaca. Keterampilan literasi membaca di SDN Krikilan 1 Masaran belum optimal. Hal ini diketahui dari nilai pre-test Literasi Membaca siswa kelas 5 yang masih dibawah 50, rata-rata 44,4. Kegiatan Pengabdian kepada Masyarakat dari program Kampus Mengajar 5 (KM 5) bertujuan untuk meningkatkan kemampuan literasi membaca siswa kelas 5 sekaligus meningkatkan nilai AKM. Kegiatan pelatihan dan pendampingan ini dilakukan melalui ceramah, demonstrasi, permainan dan diskusi dengan bantuan berbagai jenis media pendukung pembelajaran seperti permainan, scrapbook dan buku cerita. Selanjutnya, biasakan membaca buku cerita, scrapbook, dan menjawab pertanyaan-pertanyaan di dalamnya serta membuat rangkuman. Hasil post-test menunjukkan peningkatan rata-rata sebesar 86,17 hal ini menunjukkan adanya peningkatan literasi membaca siswa kelas 5. Kata Kunci: Literasi Membaca, media permainan, media scrapbook